A relativização da impenhorabilidade de bens e o direito fundamental à tutela executiva efetiva no processo civil brasileiro - Santos, Leonardo Moreira (2015)
Given the difficulties encountered by the lender to the receipt of their claims in civil enforcement, this paper aims to demonstrate the need for relativization of immunity from seizure of goods in order to increase the financial liability of the debtor that will enable it to comply with the their obligations, and therefore the lender receives your credit, given that the credit receipt in civil enforcement it is a fundamental right. The affirmation of the existence of the fundamental right of the lender was only possible with the literature, in which legal experts confirmed the need for executive protection, making it clear that the relativization of immunity from seizure of the assets so that the adjudication occurs effectively it takes to creditors in the civil enforcement procedure.